2019
DOI: 10.1016/j.jbspin.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Adverse consequences of low-dose methotrexate medication errors: data from French poison control and pharmacovigilance centers

Abstract: This study confirms that dosing errors with methotrexate can be lethal and persisted despite several warnings from drug agencies. Further measures are awaited from the European Medicine Agency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Variables associated (P < .05) with seeking information from a greater number of sources were younger age, tertiary education, higher BMQ-specific MTX concerns and higher BMQ general medicine harms scores ( Figure 2B). Age, y, mean (SD) 59 (11) Age at diagnosis, y, mean (SD) 41 (14) Disease duration, y, mean (SD) 19 (11) ARAD duration, y, mean (SD) 7 (4) Arthritis condition, VAS 0-100, mean (SD) 7 In our study, as has been previously reported, 9 patients may commonly utilize the internet as a source of information about MTX.…”
Section: Mtx Information Sourcessupporting
confidence: 58%
See 1 more Smart Citation
“…Variables associated (P < .05) with seeking information from a greater number of sources were younger age, tertiary education, higher BMQ-specific MTX concerns and higher BMQ general medicine harms scores ( Figure 2B). Age, y, mean (SD) 59 (11) Age at diagnosis, y, mean (SD) 41 (14) Disease duration, y, mean (SD) 19 (11) ARAD duration, y, mean (SD) 7 (4) Arthritis condition, VAS 0-100, mean (SD) 7 In our study, as has been previously reported, 9 patients may commonly utilize the internet as a source of information about MTX.…”
Section: Mtx Information Sourcessupporting
confidence: 58%
“…[8][9][10] The use of MTX for treatment of inflammatory disorders has generated negative publicity. 11,12 These misconceptions relate to documentation of misuse 13,14 or myths 15 obtained from other sources. Deaths due to MTX in Australia were commonly a result of dosing errors despite implementation of safety initiatives.…”
mentioning
confidence: 99%
“…Despite the fact that the proportion of patients treated with MTX in our cohort was higher than that in the Study of Belimumab in Subjects with SLE (BLISS) trials (7–21.2%) , only 50% of the potentially eligible patients with articular disease and 41% of those with mucocutaneous disease in the present study had previously received MTX. This may reflect a more limited experience with this drug of the nephrologists involved in this study as well as safety concerns related to MTX use . Moreover, according to the timing of reimbursement approval from the Italian and UK Health Systems, 5% of the patients in our cohort would have been eligible for belimumab but were treated with RTX, which may have been the consequence of a greater experience with RTX of the investigators involved in this study.…”
Section: Discussionmentioning
confidence: 99%
“…National organisations in France, Canada, and Australia have also issued advice to prescribers, similar to the NHS; also similar to the findings presented here, deaths and other errors associated with methotrexate prescribing continue to occur in these countries. [22][23][24] Implications for research and practice Previous work across several countries has resulted in a variety of suggested approaches to minimising the risks involved with methotrexate prescribing, 22,23,25 and the EMA has recently issued further guidance. 4,5 NHS Improvement has classed overdoses associated with methotrexate as a Never Event; 6 however, the authors found no evidence of any action taken by any national NHS body when anomalous prescribing has been detected in a region or practice; this is concerning but may, in part, be explained by the fact that the responsibility for enacting change is unclear.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%